A review of the Australian species of Ampithoe Leach, 1814 (Crustacea: Amphipoda: Ampithoidae) with descriptions of seventeen new species - Peart, Rachael A. (Zootaxa, 2007)
Ampithoe is the largest and the most complex of the ampithoid amphipod genera. The species of this genus have been recorded globally. This study reviews the Australian species of Amphithoe, increasing the known Australian fauna from three to 20 species, and provides a key and diagnoses to Australian species. The 17 new species are Ampithoe boiana sp. nov., A. cookana sp. nov., A. eremitis sp. nov., A. geographe sp. nov., A. hiana sp. nov., A. hyalos sp. nov., A. katae sp. nov., A. meganae sp. nov., A. merimbula sp. nov., A. ningaloo sp. nov., A. parakava sp. nov., A. peronana sp. nov., A. pseudongana sp. nov., A. roly sp. nov., A. rosema sp. nov., A. rotunda sp. nov. and A. ulladulla sp. nov.